The European committee for the prevention of torture and the gendered experience of imprisonment - O’Connell, Ciara (Crime, law and social change, 2021)
The European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (CPT) is a supranational prison oversight body tasked with carrying out visits to places of detention across Europe. Prisons fall within the remit of the CPT, and much like prisons themselves, CPT prison visits tend to focus on the male experience of imprisonment. However, the experience of imprisonment is inherently gendered and, as such, the experiences, treatment and needs of cisgender men do not necessarily represent those of cisgender women and transgender people in prison. Therefore, it follows that a different approach is also required when it comes to prison monitoring activities carried out by the CPT. This paper introduces CPT standards and the international legal framework on gender and imprisonment. It reflects on analysis of three years of CPT reporting to explore how the CPT considers the gendered experience of imprisonment. To this end, the paper considers the potential impact of the gender composition of CPT delegations, as well as provides a descriptive content analysis of CPT reports to determine how the CPT accounts for gender-specific treatment and conditions in prison. This paper poses questions and provides suggestions around how gender can be made more central across all human rights monitoring bodies operating in the penal field, both internationally and domestically.